Eat that frog! : 21 great ways to stop procrastinating and get more done in less time - Brian Tracy (Tata McGraw Hill Education Private Limited, 2011)
Eat that Frog is an excellent motivational book. The complaints I see by most here are along the lines that there\'s nothing new in this book. To me, there\'s nothing new in MOST self help books. After all, we each know that the way to stop procrastinating is to just do what we dread, the way to lose weight is to burn off more calories than we consume, the way to keep house is to clean and organize on a regular basis, and so on. What we seek is some motivation and some reasoning for doing what we dislike doing.